Open and Social Technologies for Networked Learning IFIP WG 3.4 International Conference, OST 2012, Tallinn, Estonia, July 30 - August 3, 2012, Revised Selected Papers - Ley, Tobias; Ruohonen, Mikko; Laanpere, Mart.; Tatnall, Arthur; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume constitutes the refereed post-proceedings of the IFIP WG 3.4 International Conference on Open and Social Technologies for Networked Learning, OST 2012, held in Tallinn, Estonia, in July/August 2012. The 16 full papers presented together with 3 short papers and 5 doctoral student papers were thoroughly reviewed and selected from numerous submissions. The papers cover a wide range of topics such as mobile learning, social networks, analytics and recommendations, workplace learning, learning analytics in higher education, collaborative learning in higher education, and managing open and social education.
Mobile learning -- Social networks, analytics and recommendations -- Workplace learning -- Learning analytics in higher education -- Collaborative learning in higher education -- Managing open and social education.
Keywords: Computer science; Information storage and retrieval; Education -- Data processing; Computers and civilization; Computer Science; Computers and Education; Computers and Society; Information Storage and Retrieval; Information Systems Applications (incl. Internet).